The quality of hotel service as a factor of achieving loyalty among visitors - Gajić, Tamara; Vukolić, Dragan; Zrnić, Miloš; Lóránt Dénes, Dávid (Hotel and Tourism Management, 2023)
The quality of service, as well as the impact of hotel business on achieving loyalty among hotel visitors, has always been a topic of research in the world. The aim of this research was to determine the level of service quality achieved in hotels at Mount Zlatibor, as well as whether quality factors influence the creation of loyalty among hotel visitors. The results of multiple regression analysis showed an evident influence of both tangible and intangible quality factors on loyalty. However, a slightly greater degree of influence of intangible factor was noted. Research can have theoretical and practical importance, as a complement to existing research, as well as for creating a hotel’s business strategy.